2006
DOI: 10.32398/cjhp.v4i1.742
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Agenda-Setting for Healthy Border 2010

Abstract: Policy makers take action largely on issues that attain the pinnacle of the policy agenda (Pertschuck, 2001). As a result, how decision makers choose which issues are important has been the subject of much research. Agenda-setting conceptualizes the process of how issues move from relative unimportance to the forefront of policymakers’ thoughts (Dearing & Rogers, 1996). An area within agenda-setting research, Health Promotion Agenda-Setting, provides Health Promotion practitioners with an innovative framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Kozel et al [ 32 ] developed agenda setting in the context of public health and health promotion through the process of health promotion agenda-setting [ 12 , 32 , 33 , 34 ]. Agenda setting is about the interrelationship of the domains of policy, media, and public agendas; health promotion agenda-setting is about how health issues move through agendas to the point that they become actionable by policymakers [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kozel et al [ 32 ] developed agenda setting in the context of public health and health promotion through the process of health promotion agenda-setting [ 12 , 32 , 33 , 34 ]. Agenda setting is about the interrelationship of the domains of policy, media, and public agendas; health promotion agenda-setting is about how health issues move through agendas to the point that they become actionable by policymakers [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health promotion agenda-setting shifts the focus from the traditional health education target of individual risk behavior change to the formulation and adoption of innovative health policies which advocate for the public’s health at population level [ 12 , 32 ]. Kozel et al [ 12 , 34 ], in response to an identified gap—the omission of agenda setting from health promotion planning models relating to innovation and diffusion—have developed a model of the health promotion agenda-setting process. The construction of this model includes the interrelated constructs of the media, policy, and public agendas with the integration of the seven responsibilities of health educators: assessment, planning, implementation, coordination, evaluation, acting as a resource person, and advocating for health [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Target communications and resources to leverage agenda-setting processes within a community (Kozel et al, 2003;Kozel et al, 2006aKozel et al, , 2006b; and…”
Section: Practice Element 3: Building and Sustaining Networkmentioning
confidence: 99%